US National Science and Technology Council on Impacts of Near-Earth Objects (Population and development review, 2018)
The Trump Administration has been broadly indifferent to advice from the scientific community, a stance underlined by its long delay in filling the statutory post of science adviser to the President. The Administration has sought to scale back government funding of research in many areas of science and technology, notably on climate change. An exception to these cuts, apparently justified by a potentially more dramatic connection to homeland security, is the case of impact risks of near-earth objects (NEOs). In June 2018, a working group of the National Science and Technology Council issued a brief report, titled National Near-Earth Object Preparedness Strategy and Action Plan, setting out US goals for detecting and tracking NEOs, developing deflection technologies, and recovering from impacts. (The actual work envisaged is seen as largely being undertaken nu the National Aeronautics and Space Administration, which has had a long-running program on NEOs.) Initial sections of the report are reprinted.